(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Results of syntaxonomical investigations of desert steppes vegetation of the Azovo- Syvaskyy National Nature Park are represented. Park’s vegetation consists of eleven associations that belong to four classes: Festuco-Brometea, Agropyretea repentis, Chenopodietea і Artemisietea vulgaris. Within the class Festuco-Brometea specific character of steppe phytocoenoses of the Central Syvash compared with steppe and forest- steppe zones are found. This specifity is assigned to lesser coenotaxonomical diversity, increase of coenotic role of euxerophyte floristic component and to halophyte group participation. Some conservational issues are discussed.